Parental exposure to variable saturation deficit shapes the survival and thermotolerance of Aedes aegypti eggs - Souvik Chakraborty; Dhruv Shah; Diya Dayal; Luke Lutz; Lyn Wang; Jazmin Garcia; Gabrielle Lefevre; Emily Susanto; Joshua B. Benoit (Journal of Insect Physiology, 2026)

Dehydrating microhabitats increase mite activity and intensify ectoparasitism of Drosophila - Joshua B. Benoit; Gabrielle LeFevre; Joy Bose; Ann Miller; David Lewis; Hailie Talbott; Chandrima Das; Emily Susanto; Lyn Wang; Oluwaseun M. Ajayi; Shyh-Chi Chen; Michal Polak (Journal of Comparative Physiology B, 2026)
Parasites interact with their host in variable environments that are often subject to water scarcity and dehydration. Drosophilid fruit flies and associated ectoparasitic mites interact across a range of microhabitats, typically in decaying organic matter, such as fallen fruit and cactus tissue, that dries out and deteriorates over periods ranging from days to months. Here, we report that mite parasitism of Drosophila increases with exposure to increasingly dry conditions for two fly-mite systems ( D. nigrospiracula-Macrocheles and D. melanogaster-Gamasodes ). In D. melanogaster , artificial selection for increasing behavioral resistance did not eliminate this effect, as previously selected lines remained relatively more resistant than non-selected controls even under dry conditions. Water balance assays confirmed that mites became dehydrated when held under dry conditions, which was also associated with increased mite activity. Exposure of D. melanogaster to mites dehydrated by exposure to low relative humidity increased parasitism, further supporting that prevalence of infestation intensifies under dry conditions. The results indicate that ectoparasitism in this system is affected by the water content of the mites. The increased motivation of mites to parasitize flies under dry conditions may serve to replenish mite water stores and facilitate dispersal to more favorable microhabitats.

Future warming increases the chance of success of maize-wheat double cropping in Europe - Yang Su; Ronny Lauerwald; David Makowski; Nicolas Viovy; Nicolas Guilpart; Peng Zhu; Benoit Gabrielle; Philippe Ciais (European Journal of Agronomy, 2025)

Dalbavancin as suppressive therapy for implant-related infections: a case series with therapeutic drug monitoring and review of the literature - Barthelemy Lafon-Desmurs; Benoit Gachet; Benjamin Hennart; Benjamin Valentin; Gabrielle Roosen; Maxime Degrendel; Caroline Loiez; Eric Beltrand; Piervito D’Elia; Henri Migaud; Olivier Robineau; Eric Senneville (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Effect of soybean meal enhancements on juvenile Arctic charr (Salvelinus alpinus) growth performance, gut microbiome and behavior - David Benhaïm; Clara Sauphar; Benoit Berlizot; Gabrielle Ladurée; Stephen Knobloch; Rannveig Björnsdóttir; Margareth Øverland; Alexandra Leeper (Applied Animal Behaviour Science, 2024)

Best practices for consistent and reliable life cycle assessments of urban agriculture - Erica Dorr; Benjamin Goldstein; Christine Aubry; Benoit Gabrielle; Arpad Horvath (Journal of Cleaner Production, 2023)

Life cycle assessment of eight urban farms and community gardens in France and California - Erica Dorr; Benjamin Goldstein; Christine Aubry; Benoit Gabrielle; Arpad Horvath (Resources, Conservation and Recycling, 2023)

Can N 2 O emissions offset the benefits from soil organic carbon storage? - Bertrand Guenet; Benoit Gabrielle; Claire Chenu; Dominique Arrouays; Jérôme Balesdent; Martial Bernoux; Elisa Bruni; Jean‐Pierre Caliman; Rémi Cardinael; Songchao Chen; Philippe Ciais; Dominique Desbois; et al. (Global Change Biology, 2021)
To respect the Paris agreement targeting a limitation of global warming below 2°C by 2100, and possibly below 1.5°C, drastic reductions of greenhouse gas emissions are mandatory but not sufficient. Large‐scale deployment of other climate mitigation strategies is also necessary. Among these, increasing soil organic carbon (SOC) stocks is an important lever because carbon in soils can be stored for long periods and land management options to achieve this already exist and have been widely tested. However, agricultural soils are also an important source of nitrous oxide (N 2 O), a powerful greenhouse gas, and increasing SOC may influence N 2 O emissions, likely causing an increase in many cases, thus tending to offset the climate change benefit from increased SOC storage. Here we review the main agricultural management options for increasing SOC stocks. We evaluate the amount of SOC that can be stored as well as resulting changes in N 2 O emissions to better estimate the climate benefits of these management options. Based on quantitative data obtained from published meta‐analyses and from our current level of understanding, we conclude that the climate mitigation induced by increased SOC storage is generally overestimated if associated N 2 O emissions are not considered but, with the exception of reduced tillage, is never fully offset. Some options (e.g. biochar or non‐pyrogenic C amendment application) may even decrease N 2 O emissions.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Carbon, nitrogen and Greenhouse gases budgets over a four years crop rotation in northern France - Benjamin Loubet; Patricia Laville; Simon Lehuger; Eric Larmanou; Christophe Fléchard; Nicolas Mascher; Sophie Genermont; Romain Roche; Rossana M. Ferrara; Patrick Stella; Erwan Personne; Brigitte Durand; et al. (Plant and Soil, 2011)